Pro-inflammatory role of Wnt/β-catenin signaling in endothelial dysfunction - Wadey, Kerry S.; Somos, Alexandros; Leyden, Genevieve; Blythe, Hazel; Chan, Jeremy; Hutchinson, Lawrence; Poole, Alastair; Frankow, Aleksandra; Johnson, Jason L.; George, Sarah J. (Frontiers in Cardiovascular Medicine, 2023)
Background: Endothelial dysfunction is a critical component of both atherosclerotic plaque formation and saphenous vein graft failure. Crosstalk between the pro-inflammatory TNF-α-NFκB signalling axis and the canonical Wnt/β-catenin signalling pathway potentially plays an important role in regulating endothelial dysfunction, though the exact nature of this is not defined. Results: In this study, cultured endothelial cells were challenged with TNF-α and the potential of a Wnt/β-catenin signalling inhibitor, iCRT-14, in reversing the adverse effects of TNF-α on endothelial physiology was evaluated. Treatment with iCRT-14 lowered nuclear and total NFκB protein levels, as well as expression of NFκB target genes, IL-8 and MCP-1. Inhibition of β-catenin activity with iCRT-14 suppressed TNF-α-induced monocyte adhesion and decreased VCAM-1 protein levels. Treatment with iCRT-14 also restored endothelial barrier function and increased levels of focal adhesion-associated phospho-paxillin (Tyr118). Interestingly, inhibition of β-catenin with iCRT-14 enhanced platelet adhesion in cultured TNF-α-stimulated endothelial cells and in an ex vivo human saphenous vein model, most likely via elevating levels of membrane-tethered vWF. Wound healing was moderately retarded by iCRT-14; hence, inhibition of Wnt/β-catenin signalling may interfere with re-endothelialisation in grafted saphenous vein conduits. Conclusion: Inhibition of the Wnt/β-catenin signalling pathway with iCRT-14 significantly recovered normal endothelial function by decreasing inflammatory cytokine production, monocyte adhesion and endothelial permeability. However, treatment of cultured endothelial cells with iCRT-14 also exerted a pro-coagulatory and moderate anti-wound healing effect: these factors may affect the suitability of Wnt/β-catenin inhibition as a therapy for atherosclerosis and vein graft failure.